Discourse Markers in Works of Russian Linguists: Functional-Pragmatic and Functional-Semantic Approaches - A. V. Kuleshova; T. V. Slastnikova (Научный диалог, 2024)
This article addresses the issue of discourse markers as illuminated by the works of Russian scholars. The relevance of the study is justified by the necessity of theoretical understanding of existing scientific approaches to the examination of these linguistic units. A review of scholarly works from the XX—XXI centuries is conducted. Key positions in the interpretation of discourse markers within linguistic approaches such as functional-pragmatic and functional-semantic are characterized. Attention is given to aspects of studying this linguistic phenomenon, such as terminological nomination and belonging to a language class or category. The functions of discourse markers in each of the identified approaches are discussed in the article. The polyfunctionality of individual discourse markers is noted. The results of a comparative analysis of current typologies and classifications are presented. As a result, the authors conclude on the necessity of classifying discourse markers based on several indicators of these linguistic units. The predominance of the functional-pragmatic approach in discourse marker research is acknowledged. The unresolved issue of terminological nomination is recognized. The potential for further research in the field of discourse markers from the perspective of other approaches is highlighted.